Hume’s Aesthetic Thoughts and Modern Art - Dong Cai (SHS Web of Conferences, 2023)
Modern art emerges when a new paradigm was used in art and understanding the flow of aesthetics can give an interpretation of the basic reason for this phenomenon. Through analyzing the characteristic of modern art we can discover that it conforms to the epistemology of empiricism for prioritizing sensation and etc. Hume as the epitome of empiricism in his philosophy we can summarize two ways to explain the essence of beauty, the utility theory and the empathy theory, the latter one especially works when it comes to explaining modern art. Therefore, if Cézanne is understood as an example in Hume’s way, the reason why modern art is beautiful can better eliminate its obscurity.